Making a Partnership-based Corporate Social Responsibility: PT UPC Sidrap Bayu Energi's strategy to Sustainable Community Empowerment - Ramli, Ramli; Sulvinajayanti, Sulvinajayanti; Achiruddin Saleh, Adnan; Nur Tajuddin, Fatjri (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2023)
The heightened corporate awareness regarding its social responsibility toward the community through empowerment activities is exemplified in the initiatives undertaken by PT UPC Sidrap Bayu Energi, which are executed effectively and sustainably. This research aims to explore the factors contributing to the success of corporate social responsibility in both charitable and empowerment activities within the company. To achieve this objective, a qualitative method with a phenomenological approach is employed. The study reveals that PT UPC Sidrap Bayu Energi's empowerment process entails collaboration with governmental and social community institutions, forming a network of policy makers through partnership relationships to identify community needs. The establishment of these partnership networks influences the development of activities that effectively address community challenges, aligning with government expectations for community social development. These partnership relationships with various stakeholders result in sustainable activities and serve as a conduit linking community needs, government expectations, and reinforcing the roles of social community institutions.